Tingkat Pengetahuan tentang Xerostomia pada Pasien Lansia di Puskesmas - Ariani, Dwi; Az Zahra, Septiana A. (e-GiGi, 2025)
Abstract: Xerostomia is defined as a subjective complaint of dry mouth associated with salivary gland hypofunction, mostly found among elderly. This study aimed to obtain the level of knowledge about xerostomia in elderly patients at Pasir Jaya Health Center, Cikupa, Tangerang. This was a descriptive study with a cross-sectional design using a questionnaire method (google form) consisting of an overview of the sociodemographic and health characteristics of respondents, Abbreviated Mental Test (AMT), and Summated Xerostomia Inventory Indonesia Version (SXI-ID) instruments. Respondents' knowledge was classified into three-level scales, namely good, fair and low. Data were processed with SPSS software. The results obtained 106 elderly patients as respondents. Based on the distributed questionnaires, 56 respondents (53%) had good level of knowledge and 50 respondents (47%) had moderate level of knowledge. Respondents with systemic condition as many as 76 patients (71.70%), xerogenic drug consumption 76 patients (71.70%), and status as smoker 28 patients (26.42%). In conclusion, among elderly patients at Pasir Jaya Health Center, Cikupa, Tangerang, the level of knowledge about xerostomia is classified as good and fair. The most frequent factors related to xerostomia are systemic condition and xerogenic drug consumption. Keywords: level of knowledge; xerostomia; elderly    Abstrak: Xerostomia di definisikan sebagai keluhan subjektif dari mulut kering yang berhubungan dengan hipofungsi kelenjar saliva, terutama dijumpai pada lanjut usia (lansia). Penelitian ini bertujuan untuk mengetahui tingkat pengetahuan tentang xerostomia pada pasien lansia di Puskesmas Pasir Jaya Kecamatan Cikupa Kabupaten Tangerang. Jenis penelitian ialah deskriptif edngan desain potong lintang menggunakan metode kuesioner (google form) yang terdiri dari gambaran umum karakteristik sosiodemografi dan kesehatan responden, Instrumen Abbreviated Mental Test (AMT), dan Summated Xerostomia Inventory Indonesia Version (SXI-ID). Pengetahuan responden digolongkan dalam skala tiga tingkat, yaitu baik, cukup dan rendah. Data diolah dengan software SPSS. Hasil penelitian mendapatkan 106 pasien lansia sebagai responden. Berdasarkan kuesioner yang didistribusikan sebanyak 56 responden (53%) dengan tingkat pengetahuan baik dan 50 responden (47%) dengan tingkat pengetahuan cukup. Responden dengan kondisi sistemik sebanyak 76 orang (71,70%), minum obat xerogenik 76 orang (71,70%), dan status perokok saat ini 28 orang (26,42%). Simpulan penelitian ini ialah pengetahuan mengenai xerostomia pada pasien lansia di Puskesmas Pasir Jaya Kecamatan Cikupa Kabupaten Tangerang, tergolong baik dan cukup. Faktor yang paling sering menyebabkan terjadinya xerostomia pada pasien lansia yaitu kondisi sistemik dan konsumsi obat xerogenik. Kata kunci: tingkat pengetahuan; xerostomia; lanjut usia